Korelasi Kadar Kotinin dan Kolesterol LDL Serum pada Mahasiswa Universitas Andalas - Muhammad Ihsan Fadillah; Ilmiawati Ilmiawati; Eka Fithra Elfi (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. Cigarette smoke may cause harm not only to active smokers but also to those in their vicinity (passive smokers). Cigarettes contain nicotine, which triggers the release of catecholamines, affecting lipid metabolism. Exposure to cigarette smoke may increase serum LDL cholesterol levels in active and passive smokers. Objective. This study aimed to analyze the correlation between serum cotinine (a metabolite of nicotine) and LDL cholesterol levels in young adults. Methods. A cross-sectional study was performed, the analysis included 122 Andalas University students, aged 17.5 - 25.9 years. Demographic data, smoking degree, serum cotinine, and LDL cholesterol levels were collected. Bivariate analysis was carried out individually on each independent and confounding variables to the dependent variable, followed by multiple hierarchical regressions analysis. Results. Serum cotinine levels in this study was 10,5 ± 6.8 ng/ml (mean±SD), and serum LDL cholesterol levels were 65,5±18,5 mg/dl (mean±SD). There was no significant correlation between serum cotinine and LDL cholesterol levels in bivariate analysis. However, serum cotinine levels had a nonlinear correlation with serum LDL cholesterol levels in the regression model that included body mass index (BMI) as the confounding variable. The adjusted r2 value in this study is 0,066, the standardized β coefficient for the BMI is 0,197 (p = 0.028), for the serum cotinine levels is -0,830 (p = 0.007), and for the squared serum cotinine levels is 0,753 (p = 0.014).